Facile Tailoring of Metal‐Organic Frameworks for Förster Resonance Energy Transfer‐Driven Enhancement in Perovskite Photovoltaics - Xiao Liang; Hai‐lun Xia; Jin Xiang; Fei Wang; Jing Ma; Xianfang Zhou; Hao Wang; Xiao‐Yuan Liu; Quanyao Zhu; Haoran Lin; Jun Pan; Mingjian Yuan; et al. (Advanced Science, 2024)
Abstract Förster resonance energy transfer (FRET) has demonstrated its potential to enhance the light energy utilization ratio of perovskite solar cells by interacting with metal‐organic frameworks (MOFs) and perovskite layers. However, comprehensive investigations into how MOF design and synthesis impact FRET in perovskite systems are scarce. In this work, nanoscale HIAM‐type Zr‐MOF (HIAM‐4023, HIAM‐4024, and HIAM‐4025) is meticulously tailored to evaluate FRET's existence and its influence on the perovskite photoactive layer. Through precise adjustments of amino groups and acceptor units in the organic linker, HIAM‐MOFs are synthesized with the same topology, but distinct photoluminescence (PL) emission properties. Significant FRET is observed between HIAM‐4023/HIAM‐4024 and the perovskite, confirmed by spectral overlap, fluorescence lifetime decay, and calculated distances between HIAM‐4023/HIAM‐4024 and the perovskite. Conversely, the spectral overlap between the PL emission of HIAM‐4025 and the perovskite's absorption spectrum is relatively minimal, impeding the energy transfer from HIAM‐4025 to the perovskite. Therefore, the HIAM‐4023/HIAM‐4024‐assisted perovskite devices exhibit enhanced EQE via FRET processes, whereas the HIAM‐4025 demonstrates comparable EQE to the pristine. Ultimately, the HIAM‐4023‐assisted perovskite device achieves an enhanced power conversion efficiency (PCE) of 24.22% compared with pristine devices (PCE of 22.06%) and remarkable long‐term stability under ambient conditions and continuous light illumination.